Locked and Loaded: Mechanisms Regulating Natural Killer Cell Lytic Granule Biogenesis and Release - Ham, Hyoungjun; Medlyn, Michael; Billadeau, Daniel D. (Frontiers in Immunology, 2022)
NK cell-mediated cytotoxicity is a critical element of our immune system required for protection from microbial infections and cancer. NK cells bind to and eliminate infected or cancerous cells via direct secretion of cytotoxic molecules toward the bound target cells. In this review, we summarize the current understanding of the molecular regulations of NK cell cytotoxicity, focusing on lytic granule development and degranulation processes. NK cells synthesize apoptosis-inducing proteins and package them into specialized organelles known as lytic granules (LGs). Upon activation of NK cells, LGs converge with the microtubule organizing center through dynein-dependent movement along microtubules, ultimately polarizing to the cytotoxic synapse where they subsequently fuse with the NK plasma membrane. From LGs biogenesis to degranulation, NK cells utilize several strategies to protect themselves from their own cytotoxic molecules. Additionally, molecular pathways that enable NK cells to perform serial killing are beginning to be elucidated. These advances in the understanding of the molecular pathways behind NK cell cytotoxicity will be important to not only improve current NK cell-based anti-cancer therapies but also to support the discovery of additional therapeutic opportunities.